2017
DOI: 10.4999/uhod.171706
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chemoradiotherapy at Gastric Cancer on Pancreatic Enzymes and Pancreas Volume.

Abstract: Post-operative chemoradiotherapy is one of the therapeutic approaches for operated gastric cancer. During radiotherapy planning, pancreas has not been accepted as a critical organ until now, thus toxicity to pancreas has not been considered. In our prospective study, serum pancreatic enzyme levels and pancreatic volume after RT is investigated. Seventy-one patients with gastric cancer were evaluated adjuvant chemoradiotherapy. Mean pancreas volume, mean pancreas radiotherapy dose and V5, V10, V20 and V40 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There is a wide range of pancreatic volume values from 26.14 to 153.12 cm 3 in the literature. [8,9] A study analyzing the effect of CRT at GC on pancreatic enzymes and pancreas volume measured the mean pancreatic volume as 55.79±21.71 cm 3 , as 55.59±22.19 cm 3 (26.14-153.12) in 45 Gy radiation and 56.92±22.59 cm 3 (30.60-104.43) in ≥50.40 Gy radiation [9]. In the present study, the mean pancreatic volume was 74.09±16.01 cm 3 and V40 of the pancreas had received 98.47±6.17.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a wide range of pancreatic volume values from 26.14 to 153.12 cm 3 in the literature. [8,9] A study analyzing the effect of CRT at GC on pancreatic enzymes and pancreas volume measured the mean pancreatic volume as 55.79±21.71 cm 3 , as 55.59±22.19 cm 3 (26.14-153.12) in 45 Gy radiation and 56.92±22.59 cm 3 (30.60-104.43) in ≥50.40 Gy radiation [9]. In the present study, the mean pancreatic volume was 74.09±16.01 cm 3 and V40 of the pancreas had received 98.47±6.17.…”
Section: Discussionmentioning
confidence: 99%
“…The acinar cells of the pancreas are comparatively sensitive to radiation and hence are prone to abdominal radiation toxicity in RT of gastric malignancies. [9] Chronic pancreatitis was reported even years after abdominal RT. [15] Kandaz et al [9] found that the exposure of the pancreas to a radiation dose of 5 Gy (V5) decreased the plasma amylase levels, associated with decreased risk of GC .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations